The Sasanian Empire at war Persia, Rome, and the rise of Islam, 224-651 - Decker, Michael J. (Westholme Publishing, LLC, 2022)
"The Sasanian Empire at War: Persia, Rome, and the Rise of Islam, 224-651 is the first comprehensive study in English examining war and society in one of the most important empires in world history: the Persian Empire of 224-651 AD, ruled by the Sasanian clan. At its height the Sasanians governed lands from the Indus River in the east to Egypt and the Mediterranean in the west. Adversaries of Rome, they also faced grave challenges from nomadic powers from Central Asia, notably the Huns and Turks. The Sasanians were able to maintain their empire for hundreds of years through nearly constant warfare, but when their expansion was checked in the north by the Byzantines at Constantinople in 626, and with the Muslim invasions to their south and west beginning in the 630s, the empire could no longer be sustained, and it finally collapsed. In this book, Michael J. Decker examines Sasanian warfare, including military capabilities, major confrontations, organization and weapons of the Persian army. In addition to providing a comprehensive overview of the conflicts that marked this vital period in the history of Eurasia, The Sasanian Empire at War challenges long cherished notions of the inferiority of Sasanian military capabilities and renders a new image of a sophisticated, confident culture astride the heart of Eurasia at the end of the ancient world and birth of the Silk Road. Persian arms were among the many features of their culture that drew widespread admiration and was one of the keys to the survival of Iranian culture beyond the Arab Conquest and into the present day." -- Amazon
Keywords: Geschichte 224-651; Krieg; Iran -- Altertum; Sassanids / History; Islam / History / To 1500; Iran / History, Military / To 1500; Iran / Armed Forces / History / To 1500; Rome / Army / History; Sassanides / Histoire; Islam / Histoire / Jusqu'à 1500; Rome / Armée / Histoire; Armed Forces; Islam; Sassanids; Iran; Rome (Empire); To 1500; History; Military history